Imperial Emotions Cultural Responses to Myths of Empire in Fin-de-Siècle Spain - Krauel, Javier (Contemporary Hispanic and Lusophone Cultures, 2013)
Imperial Emotions: Cultural Responses to Myths of Empire in Fin-de-Siècle Spain reconsiders debates about historical memory from the perspective of the theory of emotions. Its main claim is that the demise of the Spanish empire in 1898 spurred a number of contradictory emotional responses, ranging from mourning and melancholia to indignation, pride, and shame. By focusing on the neglected emotional dimension of memory practices, Imperial Emotions opens up new ways of interpreting some of the most canonical essays in twentieth-century Iberian literature: Miguel de Unamuno's En torno al casticismo, Ángel Ganivet's Idearium español, Ramiro de Maeztu's Hacia otra España, and Enric Prat de la Riba's La nacionalitat catalana. It also examines the profound implications the emotional attachment to imperial myths has had for the collective memory of the conquest and colonization of the Americas.